Hubungan Kecerdasan Emosi dan Pola Asuh Demokratis dengan Strategi Coping Adaptif pada Mahasiswa Tingkat Akhir - Maria Fella Thika Sary; Nefi Damayanti (Universitas Medan Area, 2019)
This research aims to know the relationship between emotional intelligence with Adaptive coping strategies, relationships with democratic parenting and adaptive coping strategies and the relationship between emotional intelligence and democratic parenting with Adaptive coping strategies on senior students. The population in this research is the senior students at the Faculty of psychology of the University of Medan Area. Sample research amounted to 74 students were taken with purposive sampling technique. The instruments used are emotional intelligence scale, parenting democratic scale and adaptive coping strategy scale. Results of multiple regression analysis shows amounted to 469.324 with Freg value p = 0.000 (p 0.005) it shows that there is a significant relationship between emotional intelligence and democratic parenting with adaptive coping strategies. Partially, there is the relationship between emotional intelligence with adaptive coping strategies with rxy = 0.00 0.936 with p , and there is a relationship between democratic parenting with adaptive coping strategies rxy = 0.920 with p 0.00. The value of R2 of 0.933 emotional intelligence means and foster democratic patterns together contributed effectively amounted to 93.3% against adaptive coping strategies.